A p53-derived apoptotic peptide derepresses p73 to cause tumor regression in vivo - Bell, Helen S. (American Society for Clinical Investigation, 2007)
The tumor suppressor p53 is a potent inducer of tumor cell death, and strategies exist to exploit p53 for therapeutic gain. However, because about half of human cancers contain mutant p53, application of these strategies is restricted. p53 family members, in particular p73, are in many ways functional paralogs of p53, but are rarely mutated in cancer. Methods for specific activation of p73, however, remain to be elucidated. We describe here a minimal p53-derived apoptotic peptide that induced death in multiple cell types regardless of p53 status. While unable to activate gene expression directly, this peptide retained the capacity to bind iASPP — a common negative regulator of p53 family members. Concordantly, in p53-null cells, this peptide derepressed p73, causing p73-mediated gene activation and death. Moreover, systemic nanoparticle delivery of a transgene expressing this peptide caused tumor regression in vivo via p73. This study therefore heralds what we believe to be the first strategy to directly and selectively activate p73 therapeutically and may lead to the development of broadly applicable agents for the treatment of malignant disease.